2012
DOI: 10.1111/j.1744-9987.2011.01032.x
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Sulfate for Relief of Pruritus in Patients on Maintenance Hemodialysis

Abstract: Pruritus is a common complaint in patients undergoing maintenance hemodialysis. The pathophysiology of pruritus in these patients is not well known, but the role of histamine release from mast cells has been reported. According to the inhibitory effects of zinc on histamine release and reported low levels of serum zinc in hemodialysis patients, we aimed to evaluate the effects of zinc sulfate for the relief of pruritus in these patients. This double-blind, randomized, placebo-controlled trial was conducted on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 6 publications
0
24
1
Order By: Relevance
“…82 In a double-blind, RCT of 40 HD patients, zinc sulfate, a medication shown to prevent histamine release from mast cells, 83 given for 2 months led to a significant improvement in CKD-aP compared to placebo. 84 However, a subsequent RCT of 36 patients did not confirm these findings. 85 …”
Section: Antihistamine Treatmentmentioning
confidence: 50%
“…82 In a double-blind, RCT of 40 HD patients, zinc sulfate, a medication shown to prevent histamine release from mast cells, 83 given for 2 months led to a significant improvement in CKD-aP compared to placebo. 84 However, a subsequent RCT of 36 patients did not confirm these findings. 85 …”
Section: Antihistamine Treatmentmentioning
confidence: 50%
“…Constant daytime and night‐time itching causes patients to experience chronic fatigue and sleeplessness and this worsens their quality of life (Kılıç Akça & Tasci, ; Najafabadi et al . , ). It was found in this study that the patients in both groups had sleep problems.…”
Section: Discussionmentioning
confidence: 97%
“…Its effect on itching in randomized trials was less than gabapentin, and its most common side effect is insomnia (14). There remains a need for a more robust evidence base for these and other agents, such as turmeric, montelukast, zinc sulfate, and nalbuphine (15)(16)(17)36).…”
Section: Discussionmentioning
confidence: 99%
“…Single randomized, controlled trials of turmeric, montelukast, and zinc sulfate have shown a significant reduction in itch compared with placebo and warrant further study (15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%